2015
DOI: 10.1001/jamadermatol.2014.3666
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Hemorrhaging in Neonatal Ulcerated Congenital Hemangioma

Abstract: These 2 cases highlight the importance of closely monitoring children with ulcerated CH because of the risk of severe bleeding. Embolization is the treatment of choice in the case of severe bleeding, as the natural history of RICH is to spontaneously regress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 16 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…There are few published reports of RICH complicated by life‐threatening bleeding. In reviewing the medical literature, we only found five other similar cases (one noninvoluting congenital hemangioma [NICH], four RICH) . Bleeding occurred early in life (10 days to 10 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…There are few published reports of RICH complicated by life‐threatening bleeding. In reviewing the medical literature, we only found five other similar cases (one noninvoluting congenital hemangioma [NICH], four RICH) . Bleeding occurred early in life (10 days to 10 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Use of embolization to treat cutaneous tumors was previously reported in 2 contexts: (1) as a pretreatment for surgical removal to decrease intraoperative blood loss 4 , 5 and (2) stabilization of acute hemorrhage from congenital hemangiomas. 6 In this case, because she was not a surgical candidate, embolization was attempted as the primary treatment rather than a pretreatment or adjunct. Although the embolization was successful in stabilizing the emergent hemorrhage, it was ultimately ineffective at curing the disease because of the rapid revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Some lesions may ulcerate, bleed or leave a scar. Other complications include pyogenic granuloma-like growth [7], a life threatening hemorrhage and thrombocytopenia [1,8]. Although most hemangiomas are isolated anomalies, several studies have reported that hemangiomas may run in families as an autosomal dominant trait suggesting the involvement of causative genetic factors [9].…”
Section: Discussionmentioning
confidence: 99%
“…They grow in utero and reach full growth at birth. On the other hand, infantile hemangiomas are more common and appear after birth [1]. Congenital hemangiomas appear in the head or limbs more often than in other locations in affected infants.…”
Section: Introductionmentioning
confidence: 99%